Gadget Use and Language Development in Children Aged 4–6 Years: A Multinomial Logistic Regression Study - Rina Ika Putri; Trisnawaty Trisnawaty; Tarmizi Thalib; A. Nur Aulia Saudi (Preventif : Jurnal Kesehatan Masyarakat, 2026)
The rapid development of technology supported by various attractive gadget features is believed to have a relationship with the golden age period in children. The multinomial logistic regression analysis revealed significant associations between gadget use intensity and language development categories. Specifically, higher gadget use was associated with increased odds of children falling into the 'appropriate' and 'questionable' language categories relative to the 'deviation' category, highlighting a complex, non-linear dynamic in digital exposure. This study aims to determine the effect of gadget use on children's language development aged 4-6 years in children. This type of research uses quantitative with descriptive analysis techniques, univariate, and multinomial logistic regression analysis. The study population was children aged 4-6 years in one kindergarten totaling 71 people and selected based on total sampling technique. The research instruments used, namely the Developmental Pre-Screening Questionnaire (KPSP) and the Gadget Use Intensity Scale. The results of this study indicate that the use of gadgets has a significant impact on children's language abilities, with a positive correlation in appropriate and questionable language skills, and a negative correlation in language abilities that show deviations. This research shows that the use of gadgets has a significant impact on the language development of children aged 4-6 years. Therefore, schools are expected to continue providing activities that stimulate children's language development, while parents are expected to monitor gadget usage at home.